Ми маємо xoy = x ^ (xlog_e y), длявсе x, інь [1, оо).

Ми маємо xoy = x ^ (xlog_e y), длявсе x, інь [1, оо).
Anonim

Відповідь:

#x = e ^ root (4) (3 журнал 5) #

Пояснення:

Враховуючи це для #x> 0 rArr x = e ^ (log x) #

і визначення # x @ y = e ^ (logx logy) #

ми маємо

# x @ x @ x = e ^ (Журнал (e ^ (Журнал (e ^ (Log ^ 2x)) Logx)) Logx) = ((e ^ (Log ^ 2x)) ^ Logx) ^ Logx #

потім

# ((e ^ (Log ^ 2x)) ^ Logx) ^ Logx = 5 ^ 3 #

тепер застосовується #log # обом сторонам

#logx log (e ^ (Log ^ 2 x)) ^ Logx = log ^ 2x log (e ^ (Log ^ 2 x)) = log ^ 4x = 3 log 5 #

потім

#log x = root (4) (3 журнал 5) # і

#x = e ^ root (4) (3 журнал 5) #